AVIAN FAUNA ALONG THREE WATER RESERVOIR FROM SATARA DISTRICT (MAHARASHTRA), INDIA - S. M. PAWAR; R. M. GANESHWADE; S. R. SONAWANE (The Bioscan, 2010)
The three reservoirs namely Kas, Kanher and Mahadare from Satara district are located near about 30 km away from city. The majority of birds were observed during winter followed by rainy and summer season. The area is inhibited by more than 95 different types of birds, out of these 33 are residential migratory or local migratory, 7 are migratory and 55 remaining birds are resident. Family Accipitridae was found dominant representing 13 species.